أهمية استثمار أقساط التأمين في تحقيق ميزة الريادة في التكلفة والسعر الأدنى في شركات التأمين - جيرار, أ. فيروز جيرار (Recherches économiques et managériales; Vol. 20 (2016): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (Decembre), 2017)
الملخص:   في إطار قيام شركة التأمين بوظيفتها في تغطية الأخطار المختلفة، تتجمع لديها أموال ضخمة تتمثل أساسا في الأقساط المدفوعة من طرف المؤمن لهم. وتعتبر هذه الأموال حقوقا لحملة وثائق التأمين، تستخدمها شركة التأمين في دفع التعويضات مستقبلا في حال تحقق الخطر المؤمن ضده. وحتى لا تبقى هذه الأموال مجمدة تقوم شركة التأمين باستثمارها في مختلف المجالات.   إن استثمار شركة التأمين لمبالغ الأقساط المتراكمة لديها يؤدي إلى تحقيق عوائد مالية هامة تساهم في تقوية مركزها المالي، كما تزيد من قدرة شركة التأمين على تخفيض التكاليف المختلفة وبالتالي إمكانية تخفيض القسط التأميني الذي يمثل سعر التأمين، الأمر الذي يجعل شركة التأمين في موضع تنافسي قوي مقارنة بالشركات المنافسة. الكلمات المفتاحية: قسط التأمين، الاستثمار في شركات التأمين، الميزة التنافسية، ميزة الريادة في التكلفة والسعر الأدنى. Abstract : In the framework of the insurance company's job to cover various risks, huge amounts of money accumulate in it which are mainly in the premiums paid by the insured party. These funds are considered the right to those who have the insurance documents, it is used by the insurance company to pay compensation in the future in case the risk insured against happens in order to prevent these funds from being frozen, insurance companies invest them in various fields.   The investment of the insurance company for the amounts of premiums accumulated  leads to significant financial returns which contribute to the strengthening of its financial position, and increase the ability of the insurance company to reduce various costs and thus the possibility of reducing the insurance premium, which represents the price of insurance, which makes the insurance company  in a strong competitive position in comparison with  competitive companies.  Key words: insurance premium, investment in insurance companies, competitive advantage, leading edge in cost and lowest price.